Reducing Adolescent Communication Apprehension Using Systematic Desensitization: An Exposure-Based Single-Subject Design - Kuswardani, Hasna Pratiwi; Wijayanti, Wismar Rizki (Developmental and Clinical Psychology, 2025)
This study aims to reduce communication apprehension in adolescents through a systematic desensitization approach using an exposure-based single-subject design. Communication apprehension, characterized by persistent anxiety in various social situations, can hinder adolescents’ adaptive functioning both academically and socially. The subject of this study was a female adolescent who reported a high level of communication apprehension and was selected using purposive sampling. The intervention was conducted over six sessions, including assessment feedback, relaxation training, construction of an anxiety hierarchy, and gradual exposure to communication apprehension-inducing situations in a controlled setting. Data were collected through behavioral observations and self-reported communication apprehension scales using an AB framework, which consists of two primary phases: Baseline and intervention, followed by a follow-up phase conducted 1.5 months after the intervention. Descriptive analysis indicated a potential reduction in the subject’s communication apprehension following the intervention. A Substantial reduction in communication apprehension was observed, as reflected in the subject’s PRCA score, which decreased from 102 (high apprehension) at baseline to 65 (moderate apprehension) after intervention. The findings indicate that systematic desensitization can be an potential, structured, and low-risk approach for psychologist and mental health practitioners in supporting adolescents experiencing communication apprehension.